Menuju Paradigma Keamanan Komprehensif Berperspektif Keamanan Manusia dalam Kebijakan Keamanan Nasional Indonesia (Lex Jurnalica, 2008)
This paper discusses the problem of national security in Indonesia. In the aftermath of cold war, the Indonesian security problem has been evolved and became more complicated. Embracing not only security in its traditional meaning but also in non traditional meaning. However, the national security policy, particularly Indonesian comprehensive security policy, remained in its old fashion stand. Therefore, this paper offers an alternative paradigm in complementing Indonesian comprehensive security policy by emphasizing the needs to adopt human security paradigm as mentioned by UNDP in 1994.Keywords: Human Security, National Security, Indonesian